2019
DOI: 10.3390/app9235178
|View full text |Cite
|
Sign up to set email alerts
|

Malware Detection on Byte Streams of Hangul Word Processor Files

Abstract: While the exchange of data files or programs on the Internet grows exponentially, most users are vulnerable to infected files, especially to malicious non-executables. Due to the circumstances between South and North Korea, many malicious actions have recently been found in Hangul Word Processor (HWP) non-executable files because the HWP is widely used in schools, military facilities, and government institutions of South Korea. The HWP file usually has one or more byte streams that are often used for the malic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Their CNN model achieved an F1 score of 98.48–98.65%, which was superior to other machine learning models. In [ 3 ], a CNN model was proposed for malware detection of HWP files, wherein the input length is assumed to be 600 bytes. This was the first study of malware detection for HWP files using only byte streams, and achieved an F1 score of 93.33–93.45%.…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…Their CNN model achieved an F1 score of 98.48–98.65%, which was superior to other machine learning models. In [ 3 ], a CNN model was proposed for malware detection of HWP files, wherein the input length is assumed to be 600 bytes. This was the first study of malware detection for HWP files using only byte streams, and achieved an F1 score of 93.33–93.45%.…”
Section: Related Workmentioning
confidence: 99%
“…The previous studies that applied a CNN model to byte streams were successful in some sense, but may not be useful when the byte streams are very long. For example, we may have to run the model proposed in [ 3 ] numerous times (about hundreds times) to make a decision for a single file. Indeed, we found that the mean stream length of PDF files of [ 6 ] is about 600, whereas the mean stream length of HWP files used in [ 3 ] is about 350,000–710,000 with a standard deviation of 2,000,000–4,000,000.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations